Chapter 32: Qualitative comparative analysis (QCA) - Thiem, Alrik (Edward Elgar Publishing, 2022)
Qualitative Comparative Analysis (QCA) is a configurational comparative method that is still hotly debated among scholars. Nonetheless, the method has made major inroads into the field of International Relations. The present chapter has three main goals. First, it argues that QCA can add significantly to our accumulation of knowledge about cause-effect relations. Second, using an existing study on contributions to military missions of the European Union, it demonstrates the functionality and workings of QCA in order to give applied researchers concrete technical guidance on how to employ the method correctly. Third and last, the chapter briefly introduces Coincidence Analysis (CNA) and Combinational Regularity Analysis (CORA) ,Äì two more recent configurational methods that have solved many of the methodological and technical problems QCA still remains affected by.